Development of Digital Pop Up Book Media to Minimize Misconceptions about the Digestive System in Elementary School Science Learning - Fitriana, Vitasya Salwa; Desstya, Anatri (Universitas Muhammadiyah Surakarta, 2025)
Science learning in elementary schools aims to instill a correct understanding of concepts so that students avoid misconceptions. However, in the digestive system material, many misconceptions are still found, for example the function of organs, the sequence of processes, and digestive disorders. One way to overcome this is to use learning media. However, so far learning media to minimize misconceptions are still rarely found. This study aims to 1). Describe the design of digital Pop-Up Book media on the digestive system material, 2). Test the validity of digital pop-up book media on the digestive system material based on the results of expert validity assessments, 3). Test the practicality of using digital pop-up books with dynamic simulations as learning media. This type of research is Research and Development (R&D) with a 4D model (define, design, develop, disseminate), which is limited to the Develop stage. The research subjects included teachers, fifth grade students of Muhammadiyah 2 Surakarta Elementary School, and expert validators. Data were collected through observation, interviews, questionnaires, pretests, and documentation. Data analysis techniques were qualitative data analysis in the form of (data reduction, data presentation and conclusion drawing). quantitative data analysis in the form of pre-test, validity test, and product practicality. The results of the study showed that 1) The media developed was a PowerPoint-based Digital Pop-Up Book containing interactive illustrations, 2D visuals, and animations of the digestive process. 2). The validity of the Digital Pop Up Book Media was declared